2016
DOI: 10.1021/acs.inorgchem.6b01668
|View full text |Cite
|
Sign up to set email alerts
|

Oxidative Addition of Disulfides, Alkyl Sulfides, and Diphosphides to an Aluminum(I) Center

Abstract: The aluminum(I) compound NacNacAl (1) reacts with diphenyl disulfide and diethyl sulfide to form the respective four-coordinate bis(phenyl sulfide) complex NacNacAl(SPh)2 (2) and alkyl thiolate aluminum complex NacNacAlEt(SEt) (3). As well, reaction of 1 with tetraphenyl diphosphine furnishes the bis(diphenyl phosphido) complex NacNacAl(PPh2)2 (4). Production of 3 and 4 are the first examples of C(sp(3))-S and R2P-PR2 activation by a main-group element complex. All three complexes were characterized by multinu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
28
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 37 publications
(29 citation statements)
references
References 64 publications
1
28
0
Order By: Relevance
“…Moreover, reactions of LM (M=Al, Ga, In) with distibine Et 4 Sb 2 occurred with insertion of LM into the Sb−Sb bond and formation of LM(SbEt 2 ) 2 . Comparable findings were reported for reactions of LAl with diphosphines, whereas the reaction of LGa with [Cp*Sb] 4 (Cp*= C 5 Me 5 ), in which the Sb atoms adopt the formal oxidation state +I, yielded [(LGa) 2 (μ,η 2:2 ‐Sb 4 )] . Interestingly, analogous reactions with the stronger reducing Mg I reagents occurred with formation of [(LMg) 4 (μ 4 ,η 2:2:2:2 ‐Sb 8 )] and [(L′Mg) 4 (μ 4 ,η 2:2:2:2 ‐Sb 8 )] (L′=HC[C(Me)N(2,4,6‐Me 3 C 6 H 2 )] 2 ), containing the Zintl‐type [Sb 8 ] 4− anion, as well as [(L′′Mg) 4 (μ 4 ,η 1:2:2:2 ‐Sb 4 )] (L′′= i Pr 2 NC[N(2,6‐ i Pr 2 C 6 H 3 )] 2 ) containing a [Sb 4 ] 4− tetraanion, respectively …”
Section: Introductionmentioning
confidence: 87%
“…Moreover, reactions of LM (M=Al, Ga, In) with distibine Et 4 Sb 2 occurred with insertion of LM into the Sb−Sb bond and formation of LM(SbEt 2 ) 2 . Comparable findings were reported for reactions of LAl with diphosphines, whereas the reaction of LGa with [Cp*Sb] 4 (Cp*= C 5 Me 5 ), in which the Sb atoms adopt the formal oxidation state +I, yielded [(LGa) 2 (μ,η 2:2 ‐Sb 4 )] . Interestingly, analogous reactions with the stronger reducing Mg I reagents occurred with formation of [(LMg) 4 (μ 4 ,η 2:2:2:2 ‐Sb 8 )] and [(L′Mg) 4 (μ 4 ,η 2:2:2:2 ‐Sb 8 )] (L′=HC[C(Me)N(2,4,6‐Me 3 C 6 H 2 )] 2 ), containing the Zintl‐type [Sb 8 ] 4− anion, as well as [(L′′Mg) 4 (μ 4 ,η 1:2:2:2 ‐Sb 4 )] (L′′= i Pr 2 NC[N(2,6‐ i Pr 2 C 6 H 3 )] 2 ) containing a [Sb 4 ] 4− tetraanion, respectively …”
Section: Introductionmentioning
confidence: 87%
“…[15] There have been previous computational studies that have investigated the energetics of s-a nd p-bond activation by the NacNacAl I complex through direct oxidative addition. [17,[20][21][22][23] However, this work is the first to shed light on the explicit role of the aromatic solvent molecule, and show how it is able to considerably enhancethe potency of the NacNacAl I system.…”
Section: Introductionmentioning
confidence: 93%
“…[12][13][14] This was employed recently by Nikonov and co-workerst oa ctivate the HÀH, HÀP, HÀN, HÀO, HÀSi, HÀB, and HÀC s bonds. [15] More recently,t he group of Nikonova lso showed that the NacNacAl I complex could activate even stronger s bonds, such as CÀF, CÀO, [16] PÀP, and CÀS, [17] and p bonds, such as C=Sa nd P=S. [18] It is believed that activation proceeds at as ingle group 13 metal center.…”
Section: Introductionmentioning
confidence: 99%
“…Crystal structure of species 11 (2,6-diispropylphenyl bulk and benzophenone scaffold are minimized, whereas hydrogen atomsa re omitted for clarity). Selectedbond lengths []a nd angles [8]: Al1ÀN1 1.876(2),A l1ÀN2 1.884(2), Al1ÀN3 1.842(2), Al1ÀO1 1.741(2), N3ÀC30 1.271(3),C30ÀC31 1.508(3), C30ÀC37 1.592(2), C37ÀO1 1.420(2);N 1-Al1-N2 97.73 (7), N3-Al1-O1 94.20 (7), C38-C37-C44 114.7(2), C31-C30-C37 121.9 (7).…”
Section: Scheme6preparation Of Compound 10mentioning
confidence: 99%
“…Activation of strong bonds by reduced main-group compounds has received significant attention [1] in the contexto f development of main-group surrogates for the common transition-metal-based catalysts. [2] In this context, NacNacAl (1, (NacNac = [ArNC(Me)CHC(Me)NAr] À ,A r= 2,6-iPr 2 C 6 H 3 ), [3] ad iketiminate-supported Group 13 carbenoid, [4] is noteworthy because of its well-documented propensityt oc leave strongH ÀX bonds, [5] CÀFa nd CÀOb onds, [6] EÀE( E = S, P) bonds, [7] and even the C=X( X= S, N) multiple bonds in thiourea andg uanidines. [8] With other multiple bonds, compound 1 showeda wealth of reactivity in coordination of alkynes [9] and alkenes [10] and in cyclizationw ith heterocumulenes.…”
Section: Introductionmentioning
confidence: 99%